Flexible and navigable suction ureteral access sheath versus traditional ureteral access sheath for flexible ureteroscopy in renal and proximal ureteral stones: a meta-analysis of efficacy and safety - Qiang Liu; Ting Zeng; Shuxia Zhu (BMC Urology)
Abstract Background Traditional ureteral access sheaths (T-UAS) are limited by rigidity and lack of suction, potentially increasing complications. Flexible and navigable suction ureteral access sheaths (FANS-UAS) offer improved maneuverability and active suction, but comparative evidence on their efficacy and safety is scarce. This meta-analysis evaluates FANS-UAS versus T-UAS in flexible ureteroscopy (fURS). Methods A systematic search across PubMed, Embase, Cochrane Library, and Web of Science (from inception to February 2025) identified studies comparing FANS-UAS and T-UAS. Included were RCTs and observational studies with ≥ 20 patients. Outcomes included stone-free rates (SFRs), operative time, hospital stay, and complications. Study quality was assessed using the Jadad Scale for RCTs and Newcastle-Ottawa Scale (NOS) for observational studies. Results Eight studies (1 RCT, 7 observational; 1,816 patients: 866 FANS-UAS, 950 T-UAS) were analyzed. Compared to T-UAS, FANS-UAS demonstrated significantly higher stone-free rates (SFRs) at both postoperative day 1 (OR = 4.01, 95% CI: 1.98–8.11) and 30-day follow-up (OR = 2.37, 95% CI: 1.62–3.46). FANS-UAS was associated with a lower risk of postoperative fever (OR = 0.31, 95% CI: 0.21–0.47). Operative time trended longer with FANS-UAS (MD = 2.64 min, 95% CI: −2.56 to 7.84; p = 0.32), though without statistical significance, while hospital stay showed no difference between groups (MD = − 0.07 days, 95% CI: −0.16 to 0.01; p = 0.1). Conclusion FANS-UAS provides superior stone clearance and reduced complications versus T-UAS, with only slightly longer operative time. The integrated suction system enables these advantages through improved fragment removal and pressure control. Further RCTs should confirm these benefits.